Three Essays in Housing Markets - (:unkn) unknown (My University, 2013)
The 2007 collapse of housing price and subsequent recession highlighted the fundamental role housing plays in the economy. Housing is not only one of the largest single expenditures most consumers have but also has a large impact on both local and national economies. In this dissertation I investigate three aspects of the housing market. The first essay shows the role that government policy can have in impacting housing prices and rents through an examination of the Arizona immigration enforcement legislation of 2010. I show that the implementation of the legislation had a negative impact on Arizona's rents and housing prices, resulting in an estimated loss of $40 billion in lost wealth from owner-occupied properties and $13.8 billion in lost rental income. In my second essay I investigate the dynamic relationship between Real Estate Investment Trusts (REITs) and housing prices. I find that the series are cointegrated and that REITs adjust to changes in their shared cointegrating relationship. I then use this finding to show that the cointegrating residual improves upon one-period ahead out-of-sample forecasts of REIT returns. In my third essay I investigate the role of macroeconomic announcements on high-frequency REIT returns. I use the forecast errors for a AR(1) rolling forecast as proxies for the surprise associated with an announcement. In addition, I use the Quandt-Andrews breakpoint test to determine changes in the announcement effect regimes. I argue that this is better than defining ad hoc regimes based on states of the business cycle when estimating the effect of macroeconomic announcements. The results indicate that macroeconomic announcements do have a real impact on REIT returns, and thus REITs do reflect market fundamentals.
Keywords: Announcement Effects; Cointegration; Hedonic Price Index; Housing; Real Estate Investment Trusts